Differentiating primary bone marrow failure syndromes in children: a retrospective analysis of early clinical and laboratory features - Leng, Yan-Li; Zhao, Yu-Qi; Li, Hong-Juan; Gu, Yan; Han, Yan; Ding, GuYu; Zhang, Xiaoyue; Li, Xu; Feng, Hui-Di; Lin, ZiYun; Zhao, Xiao-Wei; Wang, Hong-Mei (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the early clinical characteristics of different subtypes of primary bone marrow failure syndrome (BMFS) in children and identify predictive factors for early diagnosis, thereby improving the ability to differentiate BMFS at an early stage.MethodsA retrospective analysis was conducted on the clinical and laboratory data of children with primary BMFS who received regular follow-up visits exceeding one year at the First Affiliated Hospital of Shandong First Medical University from January 2020 to September 2024. Based on long-term follow-up results, the children were reclassified into subgroups, and early clinical features, blood counts, and bone marrow examination results were compared across groups. Univariate and multivariate analyses were performed.ResultsA total of 167 pediatric patients with primary BMFS were included in this study, of whom 112 (67.1%) were diagnosed with aplastic anemia (AA), 34 (20.3%) with refractory cytopenia (RCC), and 21 (12.6%) with idoipathic cytopenia of undetermined significance (ICUS). Significant statistical differences were observed among the three groups in terms of gender, red blood cell and platelet transfusion volumes within the first three months of disease onset, infection incidence, initial platelet and neutrophil counts, the lowest platelet and neutrophil values during the early stage of the disease, initial reticulocyte (RET) count and percentage, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW), bone marrow cellularity, number of megakaryocytes, enzyme-linked tissue staining for megakaryocytes, and dysplasia in bone marrow smears (p < 0.05). Among these, gender, initial RET count, and bone marrow cellularity were identified as independent predictors for AA (p < 0.01).ConclusionEarly manifestations of pediatric BMFS are characterized by pancytopenia and bone marrow hematopoietic failure; however, different subtypes exhibit variations in early clinical features and laboratory findings. Early identification of these characteristics may improve diagnostic accuracy and facilitate more effective clinical management.